Metabolomic Profiling for Histologically Fibrotic Stage in Chronic Drug-Induced Liver Injury - He, Xian; Zhou, Ming-Xi; Cheng, Cheng; Li, Shan-Shan; Gao, Yuan; Ma, Zhi-Tao; Song, Xin-Hua; Bai, Zhao-Fang; Zou, Zheng-Sheng; Xiao, Xiao-He; Wang, Jia-Bo; Lu, Ya-Wen (Frontiers in Pharmacology, 2022)
Background & aims: Chronic drug-induced liver injury (DILI) is a rare but under-researched adverse drug reaction-related disease, which is highly likely to develop liver fibrosis and even cirrhosis. In this study, metabolomics was used to screen out characteristic metabolites related to the histological progression of fibrosis in chronic DILI, and analyze the metabolic changes during the development of fibrosis for explaining the underlying mechanism. Methods: Chronic DILI patients who underwent liver biopsy were divided into different fibrosis grades. Serum was analyzed by untargeted metabolomics to find serological characteristic metabolite fingerprints. The screened fingerprints were validated by the validation group patients and compared with FibroScan. Results: 31 metabolites associated with fibrosis and 11 metabolites associated with advanced fibrosis were identified. The validation group confirmed the accuracy of the two metabolite fingerprints [area under the curve (AUC) value 0.753 and 0.944]. And the fingerprints showed the ability to distinguish the grades of fibrosis by comparing with FibroScan. The metabolite fingerprint pathway showed that bile acid synthesis is disturbed while lipid metabolism is extremely active, resulting in overload of lipid metabolites in the occurrence and development of chronic DILI-associated fibrosis. Conclusions: Our metabolomic analysis reveals the unique metabolomic fingerprints associated with chronic DILI fibrosis, which have potential clinical diagnostic and prognostic significances. The metabolomic fingerprints suggest the disturbance of the lipid metabolites as the most important factor in the development of DILI fibrosis.